Water Research Productivity, Trends and Collaborations in Malaysia between 1964 to 2012 - Chew, Teong Han; Shamsir, Mohd Shahir; Yusop, Zulkifli (Journal of Research Management and Governance, 2018)
The research in water cycle management is an important endeavour in any nation’s environmental management practices. Bibliometric examination the breadth and scope of research is one way to study past research focus. This will allow establishment of prior research trends, output and performance in order to reorient future resources, improve research collaborations and research return of investment. In this study, publications that are available on online from Web of Science and SCOPUS were examined using bibliometric analysis to visualize past research focus, institutional and author collaborations, clusters of peer research networks, lead institutions associated with the water cycle management in Malaysia from 1964 to 2012. Results showed that 80% of publications were indexed in Scopus with 5277 unique authors from 814 institutions. Significant ‘alpha researcher’ phenomenon was detected where strong principal investigators do not collaborate with each other, often only linked with ‘bridging’ individual that adopt a ‘middle man’ strategy, connecting two ‘alpha researchers’ together. Although UM is historically the initiator of many water research since 1972, UPM, USM and UKM are the current research leaders. Research universities UPM, USM, UKM and UTM possess good internal collaboration while UM only interact with external collaborators, possibly due to the highly competitive nature among themselves. Analysis of research topics showed that water pollution has been a perennial research interest since the 1990s while the geological focus has been on the river and coastal areas with studies on lake and islands receiving the least attention. Future awarding of research resources should take into account these historical insights in order to improve research allocations and institutional collaborations.